Effect of creatine supplementation in the strength training - Corrêa, Daniel Alves (2014)
Ergogenic resources are often consumed in gyms dueto the purpose of provide an improved performance in certain physical activities as competitive and aesthetic. Creatine is a supplement used in strength training that aims to assist in the yield strength and muscle hypertrophy in students and / or athletes. The aim of this review is to investigate the effects of the use of creatine supplementation on strength training for such beneficial improvements to the performance of strength and hypertrophy in men with individuals experienced in training. We concludethat creatine supplementation associated with strength training for men proves to be an efficient practice that can contribute to being part during the periodization of strength training.